Oncology nursing on the move: a contemporary issue on Chinese oncology nursing in cancer care - Li, Yingyang; Yu, Wenjing; Li, Lamei; Yao, Qianqian; Jiang, Kexin; Zhu, Tao; Jiang, Enshe (Frontiers in Public Health, 2023)
Cancers have become the primary cause of death among Chinese residents, seriously affecting their health and life. Oncology nursing is a specialized nursing practice focusing on cancer education, prevention, screening, early detection, and palliative and hospice care. China has made tremendous progress in developing oncology nursing. However, to ensure more individuals can get cancer care, the country’s healthcare system still confronts several problems in oncology nursing that need to be addressed to ensure that more individuals can receive cancer care. This article reviews the current development of oncology nursing in China, especially in pain symptom control, palliative care, end-of-life care, education and training. The challenges faced in oncology nursing in China and the suggestions for developing oncology nursing in China are also discussed and proposed in this review. The growth of research on oncology nursing by Chinese nursing scholars and concerned policymakers is anticipated to ultimately improve oncology nursing and the quality of life of patients with cancer in China.